Osteonecrosis of the Femoral Head with Collapsed Medial Lesion. Issue 7 (January 2014) - Karasuyama, Kazuyuki; Yamamoto, Takuaki; Motomura, Goro; Nakashima, Yasuharu; Sakamoto, Akio; Yamaguchi, Ryosuke; Iwamoto, Yukihide
A 60-year-old female experienced the gradual onset of left hip pain without any triggering event. Radiographs showed vertical sclerosis in the center of the femoral head and the lesion inside the boundary demonstrated diffuse bony sclerosis. No collapse was observed at the weight-bearing portion on radiograph. However, computed tomography showed a subchondral collapse at the medial lesion. On T2-weighted magnetic resonance imaging, the necrotic lesion showed diffuse high-intensity signals that indicated a prominent repair process. Bone biopsy diagnosed osteonecrosis with associated prominent appositional bone and vascular granulation tissue.